Respuesta :
First, I should point out that g(x) should be written as g(x)=(x+2)/3, otherwise the problem is confusing.
[tex]f(x)=3x-2 \enspace g(x)=\frac{x+2}{3}[/tex]
(A) [tex]f(g(x))=3(\frac{x+2}{3})-2=x\\g(f(x))=\frac{3x-2+2}{3}=x[/tex]
(B) Since [tex]f(g(x))=x[/tex] and [tex]g(f(x))=x[/tex], it holds that
[tex]f(g(x))=g(f(x))[/tex] for all x. This means the composed functions are *identical*
A
f(g(x)) = f([tex]\frac{x+2}{3}[/tex]) = 3([tex]\frac{x+2}{3}[/tex]) - 2 = x + 2 - 2 = x
g(f(x)) = g(3x - 2) = [tex]\frac{3x-2+2}{3}[/tex] = [tex]\frac{3x}{3}[/tex] = x
B
Since both composite functions f(g(x)) and g(f(x)) equal x
This indicates that the functions f(x) and g(x) are inverse functions